Potensi Dana Waqaf dalam Meminimalisasi Tingkat Kemiskinan di Indonesia - Imama Zuchroh (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2022)
Waqf money has a very large potential to improve the welfare of the community if it is utilized and managed properly. There is some evidence that waqf cash can finance MSMEs, finance education, finance health for those in need, and even establish institutional universities. Unfortunately, the potential for cash waqf is still not optimal. This happens because of the lack of cash waqf literacy, as well as the lack of managerial ability to manage waqf assets and cash waqf wealth. This paper aims to find out what is a role model for money waqf literacy to increase awareness of waqf money to the public. The results found that there are several aspects that can shape the waqf literacy model in increasing community participation for donor cash waqf. These aspects are education, a supportive environment, a good exemplary figure, and tangible results from benefits.